2014
DOI: 10.1007/s00425-014-2040-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteome analysis of the response of ramie under N, P and K deficiency

Abstract: Ramie is an important natural fiber. There has been little research on the molecular mechanisms of ramie related to the absorption, utilization and metabolism of nitrogen (N), phosphorus (P) and potassium (K). One approach to reveal the mechanisms of N, P and K (NPK) utilization and metabolism in ramie is comparative proteome analysis. The differentially expressed proteins in the leaves of ramie were analyzed by proteome analysis after 6 days of N- and K-deficient treatments and 3 days of P-deficient treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 57 publications
2
32
0
Order By: Relevance
“…Nutrients, particularly N, P, and K, play a vital role in plant growth and production, since they are involved in many biological processes [13]. Ramie is a plant with vigorous growth and thus has a high nutrient demand [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrients, particularly N, P, and K, play a vital role in plant growth and production, since they are involved in many biological processes [13]. Ramie is a plant with vigorous growth and thus has a high nutrient demand [7].…”
Section: Discussionmentioning
confidence: 99%
“…Aulah and Malhi [15,16] reported that the absorption of N, in the form of NH 4 + , is not affected by K and that the interaction between N and K is the second most important factor after NPK for increasing crop yield, which is not further increased by the increasing concentrations of N and P without the addition of K. Deng et al [13] suggested that several metabolic activities of ramie are affected by N, P, or K deficiency. For instance, the expression of profilin is down regulated under P-deficient conditions, and this affects fiber synthesis [13,17]. Fiber fresh and dry weights were also increased by fertilizer application, particularly NPK, which is consistent with the results reported by Liu et al [18].…”
Section: Discussionmentioning
confidence: 99%
“…Gel digestion was performed according to Deng et al [25] with modiications. Protein spots with signiicant diferences in abundance were manually excised from gels.…”
Section: Protein Ms Analysis and Classiicationmentioning
confidence: 99%
“…During adventitious root formation in chrysanthemum cuttings, 3% protein was related to nitrate metabolism and 7% of hormone related [6] . Ramie adapted to NPK deficiency by promoting the intracellular flow of carbon and N, promoting the synthesis cysteine and related hormones and up regulating action protein to promote growth of the root system [7] . Genetic engineering of nitrogen assimilation has received considerable attention for its improvement of nitrogen use efficiency in crops [8] .…”
Section: Introductionmentioning
confidence: 99%